Connectivity‐based parcellation of the thalamus in multiple sclerosis and its implications for cognitive impairment: A multicenter study. Issue 7 (14th April 2015) - Bisecco, Alvino; Rocca, Maria A.; Pagani, Elisabetta; Mancini, Laura; Enzinger, Christian; Gallo, Antonio; Vrenken, Hugo; Stromillo, Maria Laura; Copetti, Massimiliano; Thomas, David L.; Fazekas, Franz; Tedeschi, Gioacchino; et al.
Abstract In this multicenter study, we performed a tractography‐based parcellation of the thalamus and its white matter connections to investigate the relationship between thalamic connectivity abnormalities and cognitive impairment in multiple sclerosis (MS). Dual‐echo, morphological and diffusion tensor (DT) magnetic resonance imaging (MRI) scans were collected from 52 relapsing‐remitting MS patients and 57 healthy controls from six European centers. Patients underwent an extensive neuropsychological assessment. Thalamic connectivity defined regions (CDRs) were segmented based on their cortical connectivity using diffusion tractography‐based parcellation. Between‐group differences of CDRs and cortico‐thalamic tracts DT MRI indices were assessed. A vertex analysis of thalamic shape was also performed. A random forest analysis was run to identify the best imaging predictor of global cognitive impairment and deficits of specific cognitive domains. Twenty‐two (43%) MS patients were cognitively impaired (CI). Compared to cognitively preserved, CI MS patients had increased fractional anisotropy of frontal, motor, postcentral and occipital connected CDRs (0.002<P<0.02). They also experienced more pronounced atrophy in anterior thalamic regions and abnormal DT MRI indices of all cortico‐thalamic tracts. Damage of specific cortico‐thalamic tracts explained global cognitive dysfunction and impairment of selected cognitive domains better than all other MRI variables. Thalamic CDR DT MRI abnormalities were correlated with abnormalities of the corresponding cortico‐thalamic tracts. Cortico‐thalamic disconnection is, at various levels, implicated in cognitive dysfunction in MS. Thalamic involvement in CI MS patients is likely related to gray matter rather than white matter damage of thalamic subregions. Hum Brain Mapp 36:2809–2825, 2015. © 2015 Wiley Periodicals, Inc.